INTERNALISASI NILAI-NILAI MODERASI BERAGAMA MELALUI TEORI ANDRAGOGI PADA MAHASISWA - Husna Lutfiah; Achmad Fadil; Rifqi Pratama Pratama; Muhammad Iqbal (PAI RAFAH, 2023)
This research is entitled "Internalization of Religious Moderation Values ​​Through Andragogy Theory towards PAI UIN Raden Fatah Palembang Students". This research focuses on the instillation of religious moderation values ​​carried out by students who are adults and in this case, the andragogy theory is a suitable theory for internalizing religious moderation for PAI UIN Raden Fatah Palembang students. The research method used is qualitative research using data collection techniques through observation, interviews, and documentation. After obtaining the required data, the researcher continues the next process, namely analyzing the data to obtain results using data analysis techniques that use the first stage, namely data reduction, and continuing with data display and drawing conclusions to obtain data results that will be validated. The data obtained is valid because it is supported by sources that are relevant to qualitative research. The internalization of the values ​​of religious moderation through andragogy theory for PAI UIN Raden Fatah Palembang students is carried out through various activities such as religious Fridays, introduction to student academic culture (PBAK), as well as materials that relate to religious moderation, namely in the Pancasila and Citizenship courses which The result is that PAI UIN Raden Fatah students behave moderately, which can be seen from the phenomena that occur.